The preliminary study on cardiac structure and function in Chinese patients with primary hyperparathyroidism - Chen, Rong; Song, An; Wang, Ou; Jiang, Yan; Li, Mei; Xia, Weibo; Lin, Xue; Xing, Xiaoping (Frontiers in Endocrinology, 2023)
Purpose: Recent evidences show that primary hyperparathyroidism (PHPT) patients have a high prevalence of cardiovascular diseases. However, the reported changes in cardiac status are inconsistent in previous studies. The present work evaluated the cardiac structure and function in PHPT patients by echocardiography. Methods: PHPT patients and age- and sex-matched healthy controls were enrolled in this case-control study. Biochemical parameters were retrospectively collected from PHPT patients. Cardiac function and structure were assessed in all subjects using echocardiography. Results: A total of 153 PHPT patients and 51 age- and sex-matched healthy controls were enrolled in this study. The mean serum calcium and parathyroid hormone (PTH) levels in PHPT patients were 2.84 ± 0.28mmol/L and 206.9 (130.0, 447.5) pg/ml, respectively. Left ventricular ejection fraction (LVEF) and early to late mitral annular velocity (E/A) were significantly lower in PHPT patients than in healthy controls (68.2±6.0 vs. 70.7±16.7%, 1.0±0.5 vs. 1.4±0.5, respectively, p both < 0.05). The left ventricular mass index (LVMI) and the relative wall thickness (RWT) were not significantly different between the two groups. However, the difference in LVEF between PHPT patients without hypertension and diabetes and the control groups disappeared. The majority of PHPT patients had normal cardiac geometry; however, a proportion of them exhibited concentric remodeling (normal LVMI, RWT≥0.42). Serum calcium, corrected calcium, ionized calcium and PTH were inversely related to E/A, whereas serum phosphorus and 24-hour urine calcium were positively related to E/A. Furthermore, biochemical parameters were not correlated with LVEF. Conclusions: These findings demonstrate that PHPT patients exhibit diastolic cardiac dysfunction reflected by decreased E/A, as well as possible cardiac structural abnormalities. The serum calcium, phosphorus, and parathyroid hormone levels may influence cardiac structure and function.